Impact of drip/trickle irrigation and hydrogel with mulch on nutrient status, yield and quality of Kinnow mandarin - KUMAR, VIJAY; CHAND, GURDEV (Journal of Soil and Water Conservation, 2023)
An experiment was conducted to find out the effect of drip irrigation and hydrogel with black polyethylene mulch on yield, quality and nutrient status of Kinnow mandarin. The experiment located at Rainfed Research Substation for Subtropical fruits Raya, Sher-e- Kashmir University of Agricultural Sciences and Technology, Jammu. The two years pooled data revealed that highest soil nitrogen and phosphorus (244.5 and 20.2 kg ha-1), Fe, Mn, Zn and Cu (23.4, 1.5, 1.9 and 0.8 mg kg-1), leaf nitrogen and phosphorus (2.58 & 0.16 %) and leaf calcium and magnesium (1.68 and 0.42 %) contents, respectively,was obtained with the application of 3 days intervals drip irrigation and 90 g hydrogel with black polyethylene mulch materials of tree. The drip irrigation and hydrogel with black polyethylene mulch produced a significantly (p=0.05) maximum improve in soil moisture content in (41% ) over control treatment. The pooled analysis data two year also indicates that 3 days drip/trickle irrigation and 90 g hydrogel with mulch observed that the highest fruit yield (33.8 kg plant-1), length (6.5 cm), breadth (7.5 cm), weight (116.5 g) and fruit quality of TSS (13.3 0Brix), ascorbic acid (28.9 mg 100g-1), reducing sugar (4.3 %), non-reducing sugar (4.4%) and total sugar (8.1%). Thus, the study indicated that of drip irrigation and hydrogel with black polyethylene mulch is most favourable for flourishing cultivation of Kinnow mandarin under sub-tropical conditions of Jammu.